The Laboratory Should Actively be Involved in the Therapeutic Drug Monitoring (TDM) Process - Aydin, Ozgur; Ellidag, Hamit Yasar; Eren, Esin; Yilmaz, Necat (Indian Journal of Pharmacy Practice)
Background: After forty years, the literature on therapeutic drug monitoring (TDM) is still contradictory. Researchers need to share their experiences to build up a concencus on basics of TDM. Material and Methods: The electronic database between 1/3/2013 and 31/12/2013 was retrospectively searched for information about TDM for carbamazepine, valproic acid, phenytoin and digoxin serum level measurements. Results: 184 carbamazepine, 283 valproic acid, 64 phenytoin and 135 digoxin tests were performed. Neurology Department requested 59% of total anti-epiteptics. 48% of digoxin requests were from Emergency and Intensive Care Units. 101 (55%) of carbamazepine results and 43 (68%) of phenytoin results were in the sub-therapeutic range; 158 (56%) of valproic acid results were in the therapeutic and 55 (41%) of digoxin results were in above therapeutic range. Conclusion: The study results suggested that digoxin tests were mostly requested to confirm drug toxicity while neuorologic drug requests mostly aimed to manage drug dosage. Percentage of test requests were in line with some of the previous studies and contrary to some others. A request form including the information about the drug dosage and dosing interval, the patient’s response, indication for TDM is strongly suggested by the authors of this study. The laboratory should be able to read this basic information in order to be actively involved in test process.
Keywords: Therapeutic; Drug monitoring; Carbamazepine; Valproic acid; Phenytoin; Digoxin